PENINGKATAN KEMAMPUAN KARYAWAN MELALUI PENGEMASAN DAN MANAJEMEN KEUANGAN PADA INDUSTRI KERIPIK BUAH-BUAHAN - A. Zainul Arifin; Sulistyawati Sulistyawati; Deny Utomo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2015)
Olivia Jaya and Afalia Jaya is an industry that moves on the chips fruits. The lack of knowledge about the packaging and good financial management in industrial chips fruits cause the product unattractive and archive financial management is not arranged. Training on packaging and financial maanjemen is appropriate for the conditions in the industry Olivia Jaya and Afalia Jaya. Packaging is focused on appropriate ways and correct packaging, so that the resulting product is attractive and the quality remains. Financial management training focused on the use of computers for financial management applications, so that the financial records will be neatly arranged. The method used is lectures and application use financial management software. Achievement on the packaging training and financial management in industrial chips fruits are mostly participants partners to implement packaging properly and can implement financial management through a computer.